2016
DOI: 10.3402/qhw.v11.30160
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of seasonal changes, nature, and animals for adolescent girls’ wellbeing in northern Finland: A qualitative descriptive study

Abstract: Wellbeing is complex, holistic, and subjectively perceived. Issues such as gender, age, and environment seem to affect it. Therefore, the aim of this qualitative study was to describe the meaning of seasonal changes, nature, and animals towards 13–16-year-old girls’ wellbeing in Northern Finland. In the spring of 2014, through purposive sampling, a total of 19 girls participated in semi-structured interviews from various parts of Northern Finland. The data were analysed using content analysis. Afterwards, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…The stress-reducing effects of nature have been documented in adults in a large body of controlled experiments (see Kuo, 2015; Supplementary Material for review) and the available evidence points to a similar effect in children. Nature has been related to lower levels of both self-reported and physiological measures of stress in children (Bell and Dyment, 2008; Chawla, 2015; Wiens et al, 2016). Recently, an experimental study showed that a window view of vegetation from a high school classroom yields systematic decreases in heart rate and self-reported stress, whereas built views do not (Li and Sullivan, 2016).…”
Section: Nature May Boost Learning Via Direct Effects On Learnersmentioning
confidence: 99%
“…The stress-reducing effects of nature have been documented in adults in a large body of controlled experiments (see Kuo, 2015; Supplementary Material for review) and the available evidence points to a similar effect in children. Nature has been related to lower levels of both self-reported and physiological measures of stress in children (Bell and Dyment, 2008; Chawla, 2015; Wiens et al, 2016). Recently, an experimental study showed that a window view of vegetation from a high school classroom yields systematic decreases in heart rate and self-reported stress, whereas built views do not (Li and Sullivan, 2016).…”
Section: Nature May Boost Learning Via Direct Effects On Learnersmentioning
confidence: 99%
“…Experimental work in adults with physiological indicators shows that contact with nature offers quick and powerful reductions in stress biomarkers (e.g., Park et al, 2010 ; for review, see Kuo, 2015 ; Supplementary Materials), and this effect appears to extend to children as well. Contact with nature has been tied to lower levels of both self-reported and physiological measures of stress in multiple studies with children (Bell and Dyment, 2008 ; Chawla, 2015 ; Wiens et al, 2016 ). Recently an experimental study involving high school students showed that even a mere window view of vegetation from a classroom yields systematic decreases in both heart rate and self-reported stress, whereas a classroom without windows does not (Li and Sullivan, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A 15-min springtime walk in an urban park led to lower sympathetic nervous activity and an improved mood state in young Japanese males (mean age 21.2 years) [ 33 ]. In adolescent girls from Finland, nature evoked mainly positive feelings [ 34 ].…”
Section: Introductionmentioning
confidence: 99%